Cervical cancer recurrence: Proposal for a classification based on anatomical dissemination pathways and prognosis. (September 2019) - Bendifallah, Sofiane; de Foucher, Tiphaine; Bricou, Alexandre; Ouldamer, Lobna; Lavoue, Vincent; Varinot, Justine; Canlorbe, Geoffroy; Carcopino, Xavier; Raimond, Emilie; Huguet, Florence; Graesslin, Olivier; Touboul, Cyril; et al.
Abstract: Introduction: Precise definitions of recurrences and optimal treatment strategy are yet to be clearly defined among patients with cervical cancer (CC). The purpose of this study was to develop a reproducible classification of CC recurrence. Materiel and methods: Data of women with FIGO stages I-IV CC treated between January 2000 and January 2015 were retrospectively abstracted from nine French institutions. We proposed a rTNM classification for recurrence: locoregional (rT), nodal (rN), or distant organ (rM). According to rTNM prognosis, we then defined a rSTAGE classification (I, II, IIIA, IIIB, IVA, IVB). Results: Among the 1028 women treated for FIGO stages I-IV CC during the study period, 216 recurrences were observed (21%). The 3-year survival after recurrence was 38.8%, with a median time to recurrence of 9 months (95% CI, 30.9–48.7). A trend for a lower 3-year survival after recurrence was observed in women with multiple-site vs single-site recurrence (p = 0.1). Among the women in the rT group, a difference in 3-year survival after recurrence was found between rT1 single site, rT2 single site and rT3 single site (p = 0.02). The 3-year survival after recurrence was 69.1%, 49.2%, 37.5%, 34.2%, 23.1% and 24.4% for rStage I, II, IIIA, IIIB, IVA and IVB, respectively (p = 0.007). Conclusion: rTNM classifications and rSTAGE are discriminatory and allow all recurrence modalities to be classified. Highlights: Management guidelines for women with recurrent cervical cancer are still heterogeneous. There are many definitions of anatomical cervical cancer recurrence, complicating comparison of clinical outcomes. Homogeneous classification of cervical cancer recurrence is necessary to better define patient prognosis. We propose a classification of cervical cancer recurrence based on prognosis and dissemination pathways.